PERKEMBANGAN PONDOK PESANTREN MATHLA`UL HUDA CIWIDEY PENGUATAN TRADISI SALAFIYAH DENGAN PEMBAHARUAN MODERN - Haditsa Qur'ani Nurhakim; Isnan Rojibillah; Arif Rahman Hakim; Ilyas Rohili; Nurwajdah Ahmad; Andewi Suhartini (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
Islamic boarding schools (pesantren) are Islamic educational institutions that have played a crucial role in the history of the Indonesian nation, particularly in shaping a generation with morals, knowledge, and an active role in social life. One such boarding school that has experienced significant development is the Mathla'ul Huda Islamic Boarding School in Pasirjambu, established in 1988. This study aims to describe the history, educational system, institutional development, and social role of the Mathla'ul Huda Islamic Boarding School. The research method used a qualitative approach with descriptive analysis through document study, observation, and interviews. The results show that Mathla'ul Huda integrates the Salafiyah education system with formal schools, develops its institutions through the Muara Madani Foundation, expands its facilities and infrastructure, and makes a significant social contribution to the community. These findings confirm that Islamic boarding schools are able to adapt to the demands of the times without losing their traditional identity. This study has implications for the need to strengthen Islamic boarding school-based education policies as one of the pillars of national development.